CIPTA 2015 Annual Exhibition - Salmiah, Abdul Hamid (-, 2015)
The CIPTA 2015 exhibition, which has adopted a theme of ‘Inspiration’, is in line with the National Creative Industry Policy in embarking more efficient growth of the creative industries. ‘Inspiration’ is the result of creative ideas obtained from various sources, either through visuals or imaginations. In other words, students discover their best emerging talent through sparks of inspiration in creating something new. Inspiration will also help each student in producing their outstanding ideas and quality workmanship. The Final year students from various programs in the Faculty of Applied and Creative Arts showcase a wide range of creative and innovative projects. This year’s show will see our graduating students collaborate on a remarkable exhibition in the form of digital content, sculpture, event management, paintings, music performance, creative products, short films, documentaries and so on. This year's event was officiated by YB. Datuk Hajah Fatimah Abdullah, Minister of Welfare, Women and Family Development at the Experimental Theater, Faculty of Applied and Creative Arts, UNIMAS.